Mesoporous calcium silicate nanoparticles for superficial dental tissue reconstruction, in vitro and in vivo. Issue 40 (14th July 2021) - Gao, Yixue; Huang, Pin; Chen, Ruiying; Wang, Man; Wang, Yining; Sa, Yue; Jiang, Tao
Abstract : MCSNs could be used as a promising biomaterial for occluding the dentinal tubules in vitro and in vivo . Also, the outstanding drug delivery and antibacterial properties enable it to carry antibiotics easily for inhibiting deeper pulp infection. Abstract : The underlying dentin could be exposed to a humid atmosphere filled with bacteria if the covering enamel layer is broken because of external chemical and physical conditions. Accordingly, some diseases like bacterial invasion and dentin hypersensitivity often occur, which impact the daily life of patients. The study is aimed at evaluating the occluding effects of mesoporous calcium silicate nanoparticles (MCSNs) on the dentinal tubules in vitro and in vivo, as well as the antibacterial property and drug delivery ability when loaded with chlorhexidine (CHX) in vitro . MCSNs were synthesized according to the standard protocol. After a series of complimentary evaluations in vitro and in vivo, it was found that MCSNs and CHX–MCSNs could continually form apatite-like enamel layers on the exposed dentinal tubules and significantly reduced dentin permeability both in vitro and in vivo . Besides, MCSN and CHX–MCSN possessed low cytotoxicity in vitro, and only mild pulp inflammation was observed in two MCSNs containing groups in vivo . In addition, MCSN loaded with CHX released CHX sustainably and revealed a significant antibacterial effect against E. faecalis in vitro . Therefore, the results suggest that MCSN could be used as a promising biomaterial to occlude the dentinal tubules and carry antibiotics for avoiding further pulp infection.